Electric Wheelchair Manufacturing Analysis For Physical Disabilities Reviewed from the Aspect of Ergonomics - Mulyadi; Iswanto; Artha Gumelar, Buyung; Rudyansyah Christie, Rakhmad; Prastio, Anggit; Mustakim, Annas; Harmi Tjahjanti, Prantasi Harmi Tjahjanti (Ann Publisher, 2024)
The high rate of physical disability is a trigger and spur in the development of research/research for people with disabilities to help with their daily activities, one of which is with a wheelchair. There is a sense of concern to see manual wheelchairs used daily by people with physical disabilities, especially with their abnormal hands and feet, so it becomes a problem in itself because they are quite tricky and tired of pedaling a manual wheelchair. This condition impacts their work productivity, thereby reducing their income/economy. Therefore, the purpose of this research is to manufacture electric wheelchairs belonging to two people with physical disabilities (i.e., belonging to Bagus and Huda). The ergonomics tests are carried out, including (a) Compatibility of the anthropometry of the user's body and the dimensions of the wheelchair, (b) Results of the user's postural analysis with RULA (Rapid Upper Limb Assessment) (c) Conformity of the dimensions of the wheelchair with the standard, and (d) Evaluation of the usability of the wheelchair based on observation. The results obtained for the Bagus electric wheelchair are from the anthropometric side. The popliteal height is longer than the distance between the seat and the footrest in the wheelchair. For Bagus to be more comfortable in using his wheelchair and for his legs not to be crooked (which will potentially cause more excellent musculoskeletal disorders), it is recommended that the distance between the seat and the footrest be extended. As for Huda electric wheelchairs, in general, they have been modified to adjust to the needs and conditions of Huda's body and make the design of Huda wheelchairs more ergonomic. However, the postural analysis showed that the forearm position was raised, and the hand was twisted when Huda operated the electric wheelchair controller. It is, therefore, recommended to lower the position of the controller in line with the wheelchair mount.